CURBING CORRUPTION IN THE PUBLIC SECTOR BY UTILIZING ELECTRONIC PUBLIC ADMINISTRATION - Linhartová, Veronika (Mendel University Press, 2019)
Corruption is a highly debated issue that harms both the governments of individual countries as well as citizens themselves. Corruption in the public sector can lead to an increase in public spending and a reduction in the amount of taxes levied, thus increasing fiscal deficits and creating macroeconomic instability. Utilizing electronic administration within the public sector has recently been given much attention a key tool for fighting corruption in public administration. E-administration not only makes it possible to provide more information to the population more simply, efficiently, and quickly, but it also helps to eliminate discretion on the part of officials, i.e., the officials’ power to make decisions based on their personal assessment of a situation. This paper focuses on the relationship between a country’s corruption level and the degree of e-government being used in the country. Using graphical interpretation of statistical data and regression analysis, it was found that utilizing e-government within public administration has a positive effect on a country’s corruption level. However, economic performance demonstrated the greatest influence on the corruption level for the given period and group of countries.
Omezování korupce ve veřejném sektoru využitím elektronické veřejné správy
Keywords: corruption; corruption perception index; e-Government; e-Government Development Index; public administration; korupce; index vnímání korupce; e-Government; e-Government Development Index; veřejná správa